Chapter Moving from the margins: Palestinian mobilities, embodiment, and agency in East Jerusalem - Baumann, Hanna (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
In Jerusalem, intra-urban boundaries are experienced and negotiated in deeply embodied ways, and primarily encountered, undermined, and reinforced through mobility. Palestinians' movements are regularly restricted in areas at the geographical periphery of Jerusalem-especially those neighborhoods that have been severed from the rest of the city by the Israeli separation barrier. In expending significant energy to navigate the rules and spaces of the mobility regime, Palestinians must think of their movements from the perspective of Israeli power. This conceptual displacement of the self results in a sense of alienation, both from the spaces they cannot access and from their own capacities. Many feel stuck in both space and time and cannot envision a future for themselves in their city. Conversely, movement in spite of restrictions can also expand residents' appreciation of their own capacity. Leisure mobilities in particular bear a radical potential because they involve the enjoyment of movement through space, rather than being merely a means to an end. As Palestinians in the city assert their claim through embodied movement, they re-appropriate hostile space with light-hearted playfulness. Mobility thus emerges as a useful vehicle for examining not only how Palestinians' agency is constrained by the broader urban context but how their movements affect urban space: as they redraw the boundaries of spatial exclusion from the bottom up, they call into question who and what is considered peripheral to the city. The chapter traces the restriction of everyday movements, as well as the way marginalized residents navigate and defend contested urban terrain, using a phenomenological lens. By engaging Merleau-Ponty's view of the relationship between the body-subject and the world, it argues that everyday movements shape the spatial and temporal horizon. The restriction of movement limits what is conceivable, but at the same time, the mobility of marginal urban residents in spite of those restrictions expands the sense of what is deemed possible.